ANALISIS HUKUM PUTUSAN LEPAS DARI SEGALA TUNTUTAN (ONSLAG VAN ALLE RECHTSVERVOLGING) PADA PERKARA PERTAMBANGAN - Wahyuni Kangiden, Sri; Leonardo Lombok, Lesza; Engeline Pijoh, Feibe; Irene Lombok, Claudia (At-Tanwir Law Review, 2025)
Within the framework of a constitutional state, the judiciary holds a pivotal role in upholding the rule of law and ensuring justice through an independent and impartial judicial process. Among the various types of court rulings, the verdict of release from all legal charges (onslag van alle rechtsvervolging) is one that frequently provokes legal and public debate. This study investigates such a verdict in an illegal mining case that occurred in Ratatotok Dua Village, North Minahasa Regency, North Sulawesi, involving three defendants and adjudicated by the Tondano District Court. Despite the court establishing that the defendants' actions were proven, the panel of judges concluded that those actions did not constitute a criminal offense under the applicable laws, thereby issuing a release verdict. The objective of this research is to critically examine the legal grounds and judicial reasoning behind the issuance of the release verdict, as well as its broader implications for the enforcement of mining laws in Indonesia.